2021
DOI: 10.1007/s00259-021-05198-2
|View full text |Cite
|
Sign up to set email alerts
|

An international expert opinion statement on the utility of PET/MR for imaging of skeletal metastases

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…Specific time-signal curves have also been associated with high cellularity in whole spine perfusion in MM patients, and better correlate with viable malignancy [31] (Figure 1). A new hybrid technology combining PET and MRI has the potential to detect bone and extramedullary lesions through simultaneous metabolic and anatomic information [32]. Some studies have shown that 18 F-FDG-PET / MRI has the ability to detect medullary compression and bone lesions in patients with newly diagnosed SMM and newly diagnosed MM, with a higher diagnostic performance for MRI which detected focal lesions in 30% and 22% of PET-negative examinations [33].…”
Section: Dynamic Contrast-enhanced Mrimentioning
confidence: 99%
“…Specific time-signal curves have also been associated with high cellularity in whole spine perfusion in MM patients, and better correlate with viable malignancy [31] (Figure 1). A new hybrid technology combining PET and MRI has the potential to detect bone and extramedullary lesions through simultaneous metabolic and anatomic information [32]. Some studies have shown that 18 F-FDG-PET / MRI has the ability to detect medullary compression and bone lesions in patients with newly diagnosed SMM and newly diagnosed MM, with a higher diagnostic performance for MRI which detected focal lesions in 30% and 22% of PET-negative examinations [33].…”
Section: Dynamic Contrast-enhanced Mrimentioning
confidence: 99%
“…They clarified that FDG PET/MRI was identified as a feasible diagnostic strategy for the initial staging of rectal cancer from a costeffectiveness perspective. An international expert opinion statement has shown the utility of FDG PET/MRI for imaging skeletal metastases with several advantages compared with FDG PET/CT (higher detection, better characterization of skeletal lesions, and better delineation of extra-osseous tumor spread and spinal cord compression) [8]. They concluded FDG PET/MRI should be considered for the staging of malignancies where there is a high likelihood of metastatic osseous disease based on the characteristics of the primary malignancy, high clinical suspicious and in cases where the presence of skeletal metastases will have an impact on patient management.…”
Section: Pet/mri With Fdg In Oncologymentioning
confidence: 99%
“…Some previous studies have presented the superiority of MRI to CT in characterizing bone lesions. Thus it is expected that PSMA PET/MRI might be advantageous over PET/CT as well as in evaluating local prostate tumors [8].…”
Section: Pet/mri With Psma and Fapi In Oncologymentioning
confidence: 99%